Over‐the‐scope clips are cost‐effective in recurrent peptic ulcer bleeding. Issue 9 (1st November 2019) - Kuellmer, Armin; Behn, Juliane; Meier, Benjamin; Wannhoff, Andreas; Bettinger, Dominik; Thimme, Robert; Caca, Karel; Schmidt, Arthur
Abstract : Background: A recent prospective randomised controlled trial ('STING') showed superiority of over‐the‐scope clips compared to standard treatment in recurrent peptic ulcer bleeding. Cost‐effectiveness studies on haemostasis with over‐the‐scope clips have not been reported so far. Objective: The aim of this study was to investigate whether the higher efficacy of the over‐the‐scope clips treatment outweighs the higher costs of the device compared to standard clips. Methods: For the analysis, the study population of the STING trial was used. Costs for the hospital stay in total as well as treatment‐related costs were obtained. The average cost‐effectiveness ratio, representing the mean costs per designated outcome, and the incremental cost‐effectiveness ratio, expressing the additional costs of a new treatment strategy per difference in outcome were calculated. The designated outcome was defined as successful haemostasis without rebleeding within seven days, which was the primary endpoint of the STING trial. Average cost‐effectiveness ratio and incremental cost‐effectiveness ratio were calculated for total costs of the hospital stay as well as the haemostasis treatment alone. The cost‐effectiveness analysis is taken from the perspective of the care provider. Results: Total costs and treatment‐related costs per patient were 13, 007.07 € in the standard group vs 12, 808.56 € in the over‐the‐scope clip group ( p = 0.812) and 2084.98 € vs 1984.71 € respectively ( p = 0.663). The difference was not statistically significant. Total costs per successful haemostasis (average cost‐effectiveness ratio) were 30, 677.05 € vs 15, 104.43 € and 4917.41 € vs 2340.46 € for the haemostasis treatment. The additional costs per successful haemostasis with over‐the‐scope clip treatment (incremental cost‐effectiveness ratio) is –468.18 € for the whole treatment and –236.49€ for the haemostasis treatment. Conclusions: Over‐the‐scope clip treatment is cost‐effective in recurrent peptic ulcer bleeding.